Statistics in the field of creative industries: review of methodological basis - Z. S. Temerbulatova; A. S. Zhuparova; A. A. Nussyupayeva (Экономика: стратегия и практика)
Reliable and timely statistical information about the industry is needed, to monitor and develop strategies and programs for the economic development of creative industries. To date, the lack of international standards for collecting data on cultural industries is a major obstacle for governments that want to track the economic and social impact of creative industries, and also makes it difficult to compare internationally. The purpose of this study is to review the methodological basis for collecting statistical information in the field of creative industries. To achieve this goal, a structured literature review was carried out, as a result of which the existing methodologies for monitoring and evaluating creative industries, methods for calculating indicators of creative industries and the creative economy in international practice were analyzed. The obstacles that arise in the collection of statistics were identified, as well as the advantages and disadvantages of existing methods of collecting statistical information in the field of creative industries.